Experimental investigation of flame length of buoyancy-controlled jet flames from inclined rectangular nozzles. Issue 3 (4th May 2019) - Tao, Changfa; Shen, Yan; Ren, Jie; Zhi, Youran; Zong, Ruowen
ABSTRACT: In this paper, the buoyancy-controlled jet flames from the inclined rectangular nozzles with different aspect ratios have been investigated. The length-to-width aspect ratios of nozzles are 1, 2.25, 4, 9, and 16 with the same cross-sectional area. The inclined angles of the nozzle to the horizontal direction are 0°, 30°, 60°, and 90°. The value of flame length changes at the same inclined angle for different aspect ratios. A correlation has been developed to calculate the flame length of jet flame for different inclined nozzle and aspect ratios with an arbitrary angle.